2014
DOI: 10.1007/s00253-014-5944-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oleaginous yeast strains able to accumulate high intracellular lipids when cultivated in alkaline pretreated corn stover

Abstract: Microbial oil is a potential alternative to food/plant-derived biodiesel fuel. Our previous screening studies identified a wide range of oleaginous yeast species, using a defined laboratory medium known to stimulate lipid accumulation. In this study, the ability of these yeasts to grow and accumulate lipids was further investigated in synthetic hydrolysate (SynH) and authentic ammonia fiber expansion (AFEX™)-pretreated corn stover hydrolysate (ACSH). Most yeast strains tested were able to accumulate lipids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…Boundy‐Mills et al . screened 39 yeasts on model corn stoverhydrolyzate that contained no inhibitors but did contain xylose as well as glucose . For the nine yeasts that grew well on this medium, the authors demonstrated that the yeasts consumed both glucose and xylose faster after pre‐culturing on xylose, presumably as the yeasts have already activated the metabolic pathways for catabolising xylose so the necessary enzymes are already synthesized.…”
Section: Suitability Of Oleaginous Yeasts For Industrial Production Omentioning
confidence: 99%
“…Boundy‐Mills et al . screened 39 yeasts on model corn stoverhydrolyzate that contained no inhibitors but did contain xylose as well as glucose . For the nine yeasts that grew well on this medium, the authors demonstrated that the yeasts consumed both glucose and xylose faster after pre‐culturing on xylose, presumably as the yeasts have already activated the metabolic pathways for catabolising xylose so the necessary enzymes are already synthesized.…”
Section: Suitability Of Oleaginous Yeasts For Industrial Production Omentioning
confidence: 99%
“…141 Cryptococcus humicola produced 15 g l − 1 lipids in a total biomass weight of 36 g l − 1 . The strain (UCSEST 10-1004) came from the Phaff yeast collection at the University of California, Davis.…”
Section: Isoprenoidsmentioning
confidence: 99%
“…Oleaginous yeast have potential as a viable alternative oil-source but manufacturing for commoditybased products is cost-prohibitive mainly due to the high costs of feedstocks. Oleaginous yeast are capable of generating SCO from a variety of low-valued inedible plant-based feedstocks including corn cobs (Huang et al, 2012;Gao et al, 2014), corn residue Galafassi et al, 2012;Sitepu et al, 2014), corn fiber (Liang et al, 2014), rice straw (Huang et al, 2009), sorghum bagasse (Liang et al, 2012), sugarcane bagasse (Tsigie, 2011), and wheat straw (Yu et al, 2011). The oleaginous yeast Lipomyces starkeyi has considerable potential as a viable SCO producer due to its ability to produce high amounts of oil from hemicellulose-derived sugars including xylose (Anschau et al, 2014).…”
Section: Introductionmentioning
confidence: 99%